2013
DOI: 10.9790/0837-1415665
|View full text |Cite
|
Sign up to set email alerts
|

Parental Rejection, Personality Maladjustment and Depressive Symptoms in Female Adolescents in Pakistan

Abstract: Depressive symptoms in adolescents are matter of concern because of its high prevalence and impairment of functioning in the affected individual. Present research was conducted to examine parental rejection effect on personality maladjustment and depressive symptoms in female adolescents in Pakistan. 100 female adolescents (M = 16.03, SD = 1.74) with minor medical conditions were recruited from thee different hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
2
5
0
1
Order By: Relevance
“…Sardar and Sharifalhoseini (2014) showed that there was a significant positive correlation between self-esteem and the warmth parenting dimension. In a few studies conducted, a significant positive correlation was found between parental warmth and self-esteem, academic success, and social competence (Naz & Kausar, 2013;Suchman et al, 2007;Singh-Manoux, Fonagy, & Marmot, 2006). In our study, lower warmth scores indicate that both the children and parents need support for increasing the affiliation between the deaf children and their parents.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Sardar and Sharifalhoseini (2014) showed that there was a significant positive correlation between self-esteem and the warmth parenting dimension. In a few studies conducted, a significant positive correlation was found between parental warmth and self-esteem, academic success, and social competence (Naz & Kausar, 2013;Suchman et al, 2007;Singh-Manoux, Fonagy, & Marmot, 2006). In our study, lower warmth scores indicate that both the children and parents need support for increasing the affiliation between the deaf children and their parents.…”
Section: Discussionsupporting
confidence: 58%
“…The “rejection” theme has been thought as contrary to the “warmth” theme. The word “rejection” includes feelings such as “hatred,” “hostility,” and “irritation.” As a result of these feelings, parents treat their children brutally, depreciatory, and critically, developing negative feelings in the children (Kim, 2013; Naz & Kausar, 2013; Suchman et al, 2007). Another bipolar theme is “structure and chaos.” This bipolar theme has been built on discipline and authority.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, these results are endorsed with the results in a study 22 that depressive symptoms lead to psychological maladjustment and found strong association between depressive symptoms psychological maladjustment. In another study, Lee 23 explored sense of belongingness, resilience and depressive symptoms among alcoholics and non-alcoholics.…”
supporting
confidence: 75%
“…Few studies showed similar findings. 16,[26][27][28] The prevalence of depression among adolescents who had a family history of depression (54.5%) was more than those who did not have a family history of depression (20%). Similar findings were seen in a study conducted by Muhil M. 29 The examination related stressors like having anyone to talk to about his/ her worries, poor academic achievement and parents not agreeing with student's choice of university and career were associated with depression.…”
Section: Discussionmentioning
confidence: 99%